PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR BADAN PENDAPATAN DAERAH KOTA BEKASI - Irawan Noor; Aditya Adam Saputra (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
Bekasi City is one of the cities administratively directly adjacent to the capital city of the Republic of Indonesia, namely DKI Jakarta. Seeing this condition, it is certainly a problem in dealing with various demands for administrative services. The reason for the high demand for this service is that most people who live in Bekasi City are people who work in DKI Jakarta and cause people in Bekasi City to always compare the services provided by DKI Jakarta with Bekasi City. To maximize the services provided by the Bekasi City government, qualified human resources are needed and are able to provide the best service for the community. This study aims to analyze the simultaneous and partial effect of discipline and motivation on employee performance at the Bekasi City Regional Revenue Agency. The method used is quantitative method using regression analysis. This study involved 60 research respondents. The results of the study reveal that there is a partial or simultaneous influence of discipline and motivation on employee performance.